Sludge quality in wastewater treatment plant in Shokohieh industrial Park of Qom province in Iran - Mohammad javad Mohammadi; Ahmad Reza Yari; Mohammad Fahiminia; Narges Paidari Shayesteh; Hamed Biglari; Zohreh Doosti; Mehdi Vosoughi; Yuesf Omidi Khaniabadi (Iranian Journal of Health, Safety and Environment, 2018)
The general attitude of the wastewater treatment process in our country is focus on the effluent quality and unfortunately waste sludge quality is rarely considered. Since multiple natural hazards and routes the contact with sludge requires a comprehensive approach to protect public health and the environment. The aim of this study is an assessment of sludge management and finding out the potential use of sludge for land application. The study was conducted in January to December 2014. samples were gathered in four seasons, winter, spring, summer and autumn from wastewater treatment plant in industrial park of Shokohieh of Qom province according to the instructions in standard method. Sampling was moments and composite. Numbers of Samples were 24 that 2 samples were captured in every month. Samples measured base on standard method for water wastewater examination references and then data was analyzed by SPSS and t-test. The results show that the Physical Parameters qualities and nutrients qualities in sludge are good. The Phosphate quality is not suitable. Based on t-test, the results show that levels of fecal coliform and total coliform in cold and warm seasons are different (P